2015
DOI: 10.1002/jor.22932
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt and chromium exposure affects osteoblast function and impairs the mineralization of prosthesis surfaces in vitro

Abstract: Cobalt (Co) and chromium (Cr) ions and nanoparticles equivalent to those released through tribo-corrosion of prosthetic metal-on-metal (MOM) bearings and taper junctions are detrimental to osteoblast activity and function in vitro when examined as individual species. Here we examined the effects of Co 2þ :Cr 3þ and Co 2þ :Cr 6þ combinations on osteoblast-like SaOS-2 cellular activity, alkaline phosphatase (ALP) activity and mineralization to better reflect clinical exposure conditions in vivo. We also assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 51 publications
(104 reference statements)
1
22
1
Order By: Relevance
“…The lack of any effect of Cr 3+ alone is consistent with the observations of Kanaji and coworkers and the previously held dogma of the relative inability of Cr 3+ to cross cell‐membranes 34. In contrast to this dogma, we have previously shown the intracellular localization of Cr 3+ in osteoblasts,21 as well as an additive effect of Co 2+ and Cr 3+ treatment 22. Thus the increased effect of combined ions at 500 μg/L over the effect of Co 2+ alone observed in this study suggests for the first time potential facilitation of Cr 3+ entry into osteocytes, as well as common downstream signaling.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…The lack of any effect of Cr 3+ alone is consistent with the observations of Kanaji and coworkers and the previously held dogma of the relative inability of Cr 3+ to cross cell‐membranes 34. In contrast to this dogma, we have previously shown the intracellular localization of Cr 3+ in osteoblasts,21 as well as an additive effect of Co 2+ and Cr 3+ treatment 22. Thus the increased effect of combined ions at 500 μg/L over the effect of Co 2+ alone observed in this study suggests for the first time potential facilitation of Cr 3+ entry into osteocytes, as well as common downstream signaling.…”
Section: Discussioncontrasting
confidence: 95%
“…Periprosthetic concentrations are several fold higher (median Co, 113 μg/L; median Cr, 54 μg/L),18 while patients with failing prosthesis have reported Co and Cr concentrations as high as 528 μg/L (range: 0–13,000 μg/L) and 1,844 μg/L (range: 0–38,600 μg/L), respectively 19. We recently demonstrated that exposure to Co 2+ and Cr 3+ adversely affects both osteoclast and osteoblast survival and function, including the mineralization of prosthesis surfaces in vitro, at concentrations equivalent to those found clinically 20, 21, 22…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The adverse effects of elevated levels of metal exposure have been highlighted by the high failure rates of MOM prostheses, and by case reports of cardiac, neurological, and endocrine disorders, resulting in their recent recall from many markets . Several investigators have described the detrimental effects of metal exposure on survival and function of cell types including bone cells, monocytes, and macrophages in vitro . The mechanism by which metal debris exerts these effects is still unclear, although some investigators have studied changes in gene expression of candidate genes in cell and animal models …”
mentioning
confidence: 99%
“…11 Several investigators have described the detrimental effects of metal exposure on survival and function of cell types including bone cells, monocytes, and macrophages in vitro. [12][13][14][15] The mechanism by which metal debris exerts these effects is still unclear, although some investigators have studied changes in gene expression of candidate genes in cell and animal models. [16][17][18] Several studies have reported metal-induced changes in DNA methylation, alteration in gene expression and cell physiology in the setting of cancer.…”
mentioning
confidence: 99%